IMPROVING STUDENTS’ ABILITY ON PAST PERFECT TENSE THROUGH QUEUE TECHNIQUE: A Collaborative Classroom Action Research to the Second Year Students of SMA N 1 Peusangan Selatan - Misnawati Misnawati; Murni Murni (Jurnal Pendidikan Almuslim, 2016)
The title of this research is: Improving students’ ability on past perfect tense through queue technique (A collaborative classroom action research to the second year students of SMA N 1 Peusangan Selatan). There are two problems of the research namely: How does queue technique increase the students’ ability in mastering past perfect tense to the second year students of SMA N 1 Peusangan Selatan? and how is the students’ motivation when the queue technique applied in teaching past perfect tense to the second year students of SMA N 1 Peusangan Selatan? Based on the research problems, there are two purposes of the research, namely to know the queue technique increases the students’ ability in mastering past perfect tense to the second year students of SMA N 1 Peusangan Selatan and to describe the students’ motivation when the queue technique applied in teaching past perfect tense to the second year students of SMA N 1 Peusangan Selatan. To answer the research questions, the researcher used the Collaborative Classroom Action Research as methodology of the research. The research was conducted at SMA N 1 Peusangan Selatan, which is located in Bireuen District. The subjects of the research were the second year students of SMA N 1 Peusangan Selatan. This class consisted of twenty (20) students. The instruments of the research were tests, observation sheets and questionnaires. In the cycle I, the implementation of queue technique had not reached the predetermined criteria of success. The students’ average score for cycle I was 62.25. In cycle II, the students’ achievements have met the criteria of success. Their average score in cycle II was 73. Therefore, based on the result of collecting data, it could be concluded that the second year students of SMA N 1 Peusangan Selatan could improve their ability when the teacher uses queue technique in teaching process of past perfect tense. Key words: Past perfect tense, Queue technique